Between a Rock and Hard Place: Stakeholders’ Perspectives about the Private Provision of Higher Education - Tamrat, Wondwosen; Fetene, Getnet Tizazu (Bahir Dar Journal of Education, 2021)
This study was conducted to gauge stakeholders’ views towards the provision of private higher education in Ethiopia. More specifically, the study sought to examine stakeholders’ perception regarding the importance of private higher education; academic provisions of private higher education institutes as contrasted with the public higher education sector, and government’s role in the provision of private provision of higher education. The study followed a mixed method design employing concurrent procedures in which qualitative and quantitative data were gathered simultaneously. While quantitative data were gathered through survey questionnaire administered among 297 key stakeholders comprising parents, students, faculty, and employers, qualitative data were generated from relevant documents and in-depth interviews conducted with seven leaders of PHEIs willing to take part in the study. The results indicate that in the eyes of stakeholders, private higher education offers significant advantages in creating additional access and related benefits such as introducing improved student orientation. However, stakeholders equally observe that private higher education institutions fall far short of societal expectations due to their excessive profit-orientation and illicit behavior that demeans societal acceptance and sectoral legitimacy. It is argued that as a newly emerging sector whose viability is judged against the more experienced public sector, private higher education institutions should address their weaknesses in order to assure their viability and enhance the ‘publicness’ of their provisions.